PEMBENTUKAN KARAKTER KEWIRAUSAHAAN DENGAN KEGIATAN MARKET DAY DI SEKOLAH DASAR SOEKARNO HATTA - Badawi Badawi Badawi (Universitas Muhammadiyah Kotabumi, 2023)
The character of students must be able to reflect the culture of the Indonesian nation. The formation of character is very important in the world of education. Education must play a role in forming character in the transformation of knowledge so that Indonesian people are knowledgeable and have character. This study aims to describe the implementation of market day in the formation of entrepreneurial character in students at Soekarno Hatta Elementary School. The methodology in research on the formation of entrepreneurial character through market day activities at Soekarno Hatta Elementary School uses descriptive qualitative methods. This method attempts to describe the phenomena that occur in character building through market day activities. The subjects in this study were teachers and students of Soekarno Hatta Elementary School located at Soekarno Hatta Elementary School, Kotabumi, North Lampung. Data collection was carried out by first observing and semi-structured interviews. Data analysis techniques used data reduction and data triangulation. The results showed that market day activities were activities for forming students' entrepreneurial character values. Entrepreneurial character values ​​formed through market day activities at SD Soekarno Hatta are honest, creative, innovative, disciplined, cooperative, responsible, independent and confident. Entrepreneurial character values ​​can be formed from market day activities in the concept of character education, namely exercise of the heart, exercise of thought, exercise of taste, and exercise.